2006
DOI: 10.1016/j.jacc.2006.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1/erbB-Activation Improves Cardiac Function and Survival in Models of Ischemic, Dilated, and Viral Cardiomyopathy

Abstract: These beneficial effects make rhNRG-1 promising as a broad-spectrum therapeutic for the treatment of heart failure due to a variety of common cardiac diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
241
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(252 citation statements)
references
References 24 publications
(32 reference statements)
8
241
1
2
Order By: Relevance
“…In fact, we have shown that these MPs persist in heart tissue for at least 90 days following implantation, favoring long-term growth factor therapy [38]. The importance of this sustained release is supported by the fact that previous studies analyzing intravenous injection of free NRG1 did not observe improvements in infarct size [22], supporting the benefit of using PLGA MPs for delivery. Furthermore, while MPs were implanted by direct injection in this study, the size of the particles employed should allow for delivery through a less invasive procedure, such as using a NOGAguided catheter.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In fact, we have shown that these MPs persist in heart tissue for at least 90 days following implantation, favoring long-term growth factor therapy [38]. The importance of this sustained release is supported by the fact that previous studies analyzing intravenous injection of free NRG1 did not observe improvements in infarct size [22], supporting the benefit of using PLGA MPs for delivery. Furthermore, while MPs were implanted by direct injection in this study, the size of the particles employed should allow for delivery through a less invasive procedure, such as using a NOGAguided catheter.…”
Section: Discussionmentioning
confidence: 70%
“…Consistent with this idea, it is known that FGF1 regulates cardiac remodeling by exerting a protective and proliferative effect after MI [18,19]. On the other hand, neuregulins play crucial roles in the adult cardiovascular system by inducing structural organization of sarcomeres, cell integrity, cell-cell adhesion [20], cell survival [21,22] and angiogenesis [23]. In fact, several studies using animal models of heart failure have demonstrated the therapeutic benefits of neuregulins, which improved cardiac performance, attenuated disease markers, and prolonged animal survival [24,25].…”
Section: Introductionmentioning
confidence: 80%
“…Recombinant NRG1 (beta-2a; Zensun Sci and Tech, Shanghai, China) [5] at 50 g/kg body weight or an equivalent volume of 0.9% NaCl (sodium chloride) was administered by i.p. injection three times a week for 8 weeks (n = 8 for each group).…”
Section: Nrg1 Treatmentmentioning
confidence: 99%
“…Neuregulin1 proteins improve cardiac function in doxorubicin-treated animals (Liu et al, 2005;Liu et al, 2006;Bian et al, 2009). Comparing the two studies, we used recombinant human glial growth factor 2 (GGF2), and a subacute doxorubicin cardiotoxicity mouse model (doxorubicin, 20 mg/kg, i.p.…”
Section: Our Laboratory and Liu Et Al Further Demonstrated That Injementioning
confidence: 99%
“…Recombinant Neuregulin1 was injected i.v. daily for the first 7 days using the dosage of 20”g/kg/day (Liu et al, 2006). Despite the different isoforms of Neuregulin1, the dosage, the route of drug administration and the animal models used, both studies showed that injections of recombinant Neuregulin1 significantly improved survival and cardiac systolic function in doxorubicin-injured mice and rats.…”
Section: Our Laboratory and Liu Et Al Further Demonstrated That Injementioning
confidence: 99%